Search and research teacher education for contemporary - MENA MARCOS, Juanjo; GARCÍA-VALCÁRCEL, Ana; GARCÍA PEÑALVO, Francisco José; MARTÍN DEL POZO, Marta (Aquilafuente, 2017)
ions or in the use of digital technologies. Positive interactions lead to building strong communities of learners, which in turn, leads to the production of valuable knowledge and better understandings about learning and teaching. With the upcoming commemoration of its 800th anniversary in the year 2018, the University of Salamanca, as the oldest university in operation in Spain, is proud to host the ISATT 18th biennial conference and to support the exceptional work of many researchers in the field of Teacher Education by compiling and editing the work in this volume. Furthermore, the local Organizing Committee and the ISATT Executive Committee hope you will experience a rewarding intellectual experience as a result of your contributions and knowledge, as both academics and practitioners. Thank you very much for providing us this exciting opportunity to work with you. We warmly welcome you to Salamanca a truly historic and a contemporary context!